2013
DOI: 10.1063/1.4793282
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced phase transitions of α-Ce3Al

Abstract: A series of shock compression experiments on hexagonal α-Ce3Al have been carried out using a two-stage light gas gun. No phase transition was observed in the recovered sample shock compressed at 23.5 GPa. However, as the shock pressure was increased to 27.3 GPa, a face-centered cubic Ce3Al phase was detected in the samples recovered at ambient conditions. Furthermore, a Ce2Al phase was found in the 37.1 GPa shocked sample with a space group Fd-3m and lattice parameter a = 8.26(1) Å. These Ce-based alloys may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Over the last decade, MD simulations and experimental studies have been performed to explore solid-solid phase transformations in single crystals [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For example, Kadau et al [24] identified the role of shockwave strength on structural transformations in Ga single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, MD simulations and experimental studies have been performed to explore solid-solid phase transformations in single crystals [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. For example, Kadau et al [24] identified the role of shockwave strength on structural transformations in Ga single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 On the theoretical side, an observation that the virtual charge fluctuations in the context of Kondo model and the electron transition induced by the applied pressure in Ce 3 Al suggest that the fundamental properties could be changed by the external and internal factors. 12,16 Indeed, a first principle calculation for a similar Ce-based system has already been undertaken in previous work. 21 Theoretically, as discussed in our previous paper, 22 DFT + DMFT method could simultaneously capture the weakly, moderately, and strongly correlated strengths, and deal with the low-lying coherent and high-lying incoherent excitations within a unified framework.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental measurements and theoretical calculations on the fundamental properties such as the electronic, magnetic and mechanical properties in Ce 3 Al are favorable for its potential industrial applications, 9,10 for example, metallic glass, 11,12 shape memory alloy, 9 hydrogen storage, 12 spectrometer, 13,14 and laser‐induced phase transformation 15 . Previous experimental and theoretical works demonstrate that the unique polyamorphic transition accompanying with shrinkage of the atomic volumes in Ce–Al metallic systems because of pressure‐driven electron delocalization 12,16 . Up to date, previous articles mainly focus on the magnetic properties and the heavy fermion behaviors, 6,17 however, few works has reported the electronic properties of Ce 3 Al system 6,18 .…”
Section: Introductionmentioning
confidence: 99%
“…High pressure (HP) can input energy into a system without inducing an increase in the free volume and strongly affect the property of materials. 32 Some researches [33][34][35][36][37][38] have focused on the HP effect on MGs, especially the cerium based MGs owing to their low glass transition temperature (T g ) and weak bonding between atoms. [39][40][41] The crystallization, [42][43][44][45][46] amorphization, 47,48 and polyamorphism [49][50][51][52] of the Ce-based alloys under HP show their unique behaviors.…”
Section: Introductionmentioning
confidence: 99%